The Alteration of the Philippines Foreign Policy towards China over Disputes in the South China Sea - Yanuar, Muhammad Dedy; Priyanka Rahmmadinniyah, Anggraeni Sevira (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2022)
As one of the most protracted issues in the world politics, South China Sea (SCS) disputes have frequently sparked boiling tension among claimant states- China, Taiwan Vietnam, Malaysia, Brunei, and in particular the Philippines - one of the most assertive claimant states aside China. During the administration of President Benigno Aquino III, the Philippines managed to internationalize the case of SCS disputes and ultimately won a victory over China in the Permanent Court Arbitration (PCA), the Netherlands. However, when a government transition occurred from Benigno Aquino III to Rodrigo Duterte in 2016, those PCA credits appeared to be not followed up by President Duterte. This ensued due to the differences in views and political will between Aquino and Duterte on foreign policy. This article aims to unravel and explain on the Philippines’ foreign policy alteration towards China over SCS disputes under Duterte’s administration, using the concept of Realpolitik and Rational Choice to comprehend why President Duterte decided to seemingly abandon his predecessor’s policies. This research employed qualitative method - data collection was obtained from the secondary data and literature study, comprising written documents related to the Philippines foreign policy in responding to the disputes. The results showed that the reason why Duterte abandoned his predecessor’s footpath is because he assumed that the way Aquino applied such assertive approach is not effective enough in resolving this prolonged maritime jurisdictional disputes between the Philippines and China. In this way, Duterte applied a more considerate diplomatic approach to China as his rational choice in a sense that he would rather take cooperative instead of confrontational way of settlement in resolving the disputes of maritime territory over the South China Sea.